Science in Culture : Translated from the Polish by Hugh McDonald. - Jaroszynski, Piotr. (Value Inquiry Book Series, 2007)
This book tries to uncover science's discoverer and explain why the conception of science has been changing during the centuries, and why science can be beneficial and dangerous for humanity. Far from being hermetic, this research can be interesting for all who want to understand deeper what really conditions the place of science in culture.